2012
DOI: 10.1155/2012/404581
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Viruses in the Treatment of Bladder Cancer

Abstract: Bladder carcinoma is the second most common malignancy of the urinary tract. Up to 85% of patients with bladder cancer are diagnosed with a tumor that is limited to the bladder mucosa (Ta, T1, and CIS). These stages are commonly termed as non-muscle-invasive bladder cancer (NMIBC). Although the treatment of NMIBC has greatly improved in recent years, there is a need for additional therapies when patients fail bacillus Calmette-Guérin (BCG) and chemotherapeutic agents. We propose that bladder cancer may be an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 106 publications
0
16
0
1
Order By: Relevance
“…1 Previous studies from our lab have identified that localized expression of B18R, a gene from Vaccinia virus which encodes a secreted decoy receptor with a broad antagonizing effect against type 1 IFNs, significantly improved the efficacy of the attenuated VSVΔ51 to grow and kill tumors. 1,5,6 A number of studies have explored combination viral strategies, [7][8][9] but toxicity and safety remain a concern, as knockdown of type 1 IFN in tissues other than tumor presents the risk of susceptibility to unrestricted replication of other infecting viruses. Therefore, a tightly controlled mechanism for tumor-specific B18R production is required to facilitate this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies from our lab have identified that localized expression of B18R, a gene from Vaccinia virus which encodes a secreted decoy receptor with a broad antagonizing effect against type 1 IFNs, significantly improved the efficacy of the attenuated VSVΔ51 to grow and kill tumors. 1,5,6 A number of studies have explored combination viral strategies, [7][8][9] but toxicity and safety remain a concern, as knockdown of type 1 IFN in tissues other than tumor presents the risk of susceptibility to unrestricted replication of other infecting viruses. Therefore, a tightly controlled mechanism for tumor-specific B18R production is required to facilitate this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…This ease of access to the urothelium through the urethra also allows for frequent evaluation of treatment effects and tissue sampling . Additionally, the papillary configuration of superficial bladder cancer increases the surface area for topical application, and the bladder is an isolated organ with an asymmetric multilayered unit membrane, which limits systemic exposure to agents, thereby providing a margin of safety . Furthermore, the success of BCG therapy has shown the immunosensitivity of bladder cancer, suggesting the potential usefulness of other immunomodulating therapies .…”
Section: Clinical Trials Of Oncolytic Virus Therapy For Bladder Cancermentioning
confidence: 99%
“…Many types of oncolytic viruses have undergone preclinical studies for the treatment of urological cancers, as well as other malignancies, and some have already been tested in clinical trials . For example, a phase I trial of the third‐generation oncolytic HSV‐1, G47Δ, in patients with prostate cancer was started in 2013 and completed in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, poly-rBCG DNA vaccines that specify multiple BCG antigens such as Ag85A, Ag85B, Mpt64, and PstS3 have been developed and shown to elicit Th1-predominant immune responses, inhibit tumor growth, and prolong the survival of bladder tumor bearing mice [Lee et al 2004]. [Potts et al 2012]. Here, we focus on the following two recombinant adenovirus-based therapies: rAd-IFNα/Syn3 and CG0070.…”
Section: Bcg Subcomponent-based Rbcgmentioning
confidence: 99%